Liquid-liquid phase separation of ATXN2L enhances mRNA translation in hepatocellular carcinoma - Wang, Shenghong; Guo, Peilan; Ma, Wenqiang; Huang, Honglin; Zhang, Qianqian; Wolczynski, Slawomir; Rahman, Nafis; Liu, Jiali; Tsang, Suk-Ying; Du, Xuguang; Wang, Fengchao; Gao, Jie; et al. (Elsevier BV, 2026)
RNA-binding proteins (RBPs) serve as key regulators of hepatocellular carcinoma (HCC); however, the specific mechanisms by which RBPs function in this context require clarification. Here, we identify an RBP, ATXN2L (ataxin 2-like), that is significantly upregulated in HCC tissues and correlates with a poor prognosis. Knockdown of ATXN2L in HCC cells or knockout of Atxn2l in mice suppresses HCC progression. Mechanistically, enhanced liquid-liquid phase separation (LLPS) activity of ATXN2L results in the formation of larger ATXN2L-positive granules, which facilitate the recruitment of several eukaryotic initiation factors (eIFs) and their downstream targets, such as ADAM9 (ADAM metallopeptidase domain 9), thereby promoting mRNA translation. Moreover, the promotion of ATXN2L granules on ADAM9 translation is further enhanced via co-localization with stress granules (SGs). Together, our findings reveal that ATXN2L functions as a critical translational regulator in HCC progression through LLPS activity, which could serve as an effective therapeutic target for HCC treatment.